Combating Daesh: Insights into Malaysia’s Counter-Terrorism Experience and the Deradicalisation of Former Detainees - Mohd Irwan Syazli Saidin; Kartini Aboo Talib Khalid (Religions, 2023)
Malaysia is no exception when it comes to the Daesh threat. Several vulnerable Muslim populations have been previously targeted by Daesh via specific modus operandi to fulfil the terrorism agenda. Based on a persistent concern about Daesh-related issues and their consequences, this article critically explores the role of the security agency, the Counter-Terrorism Division within the Royal Malaysia Police (RMP), in addressing Daesh radicalisation in Malaysia. It examines the process and effectiveness of the top down and ‘soft’ approaches undertaken by the RMP via the rehabilitation and deradicalisation of former Daesh detainees before they rejoin society. The research is qualitative, and is based on a focus group discussion and in-depth interviews with representatives from the Counter Terrorism Division, terrorism experts, government officials and former detainees. The findings show that the RMP’s efforts to curb Daesh intimidation have been effective in terms of decreasing the number of new terrorism incidents, militant recruitment and the establishment of networks and cells. The introduction of ‘Module 30′, which involves theological and psychological improvement, and civil order, along with vocational training and ‘lifelong-monitoring’, has significantly contributed to rehabilitating and deradicalising the majority of former Daesh convicts in Malaysia, such that they embrace peace and renounce violence and religious extremism.